Influence of sheep breeds on the susceptibility to strongyle infection in Rajasthan - SINGH, D; SWARNKAR, C P (The Indian Journal of Animal Sciences, 2014)
A study was conducted to observe the influence of sheep breeds on the susceptibility to natural strongyle infection in Rajasthan. Faecal samples (39,896) from native, crossbred and exotic sheep managed under farm condition in both arid and semi-arid agro-climate of Rajasthan were evaluated for incidence and intensity of strongyle infection (predominated by Haemonchus contortus). In semi-arid region, parasitological profile showed relatively the lowest susceptibility of Garole and its crosses followed by Malpura, Chokla, Kheri and the highest susceptibility in crossbreds. Like-wise in arid region, the lowest susceptibility was expressed by Nali sheep followed by Marwari, Chokla, crossbreds and the highest susceptibility by exotic sheep. During wormy season, at Arid Region Campus, Bikaner, Marwari sheep possessed greater resistance compared to Magra sheep. It was also observed that similar genotype of sheep vary in susceptibility according to agroclimatic conditions and resultant pasture infectivity. The over-dispersion phenomenon in faecal egg counts suggested that inter-individual variation in susceptibility to natural infection was of more importance than inter- breed differences. Further the study suggested that for selection for resistance to GIN infection in Indian sheep under natural condition might be possible.